PENGARUH MUSIK BISING ROCK TERHADAP DAYA INGAT PADA MAHASISWA FAKULTAS PSIKOLOGI - Rahmawaty Parman; Fadhila A. Husain; Meylan Kasim; Patmawati Suleman; Rifky D. Pahrun; Salsa Veronika Koem (program studi psikologi, 2023)
This study aims to examine the ef ect of rock music noise on the memory of students of the Faculty of Psychology, University of Muhammadiyah Gorontalo using a quasi- experimental method with a static group design. A total of 30 students were divided into two groups, namely the experimental group exposed to rock music and the control group that was not exposed. The results of the analysis showed a significant dif erence in memory between the two groups, with a significance value of 0.047 (p < 0.05), which indicates that rock music noise has not a negative impact on student memory. These findings are important for understanding environmental influences on cognitive function, despite limitations in the sample size and type of noise tested